Evaluation of patients' response to pulsed radiofrequency treatment applied to the suprascapular nerve in patients with chronic shoulder pain - (:unkn) unknown (My University, 2011)
Background and objective: The aim of this study was to evaluate patient satisfaction, efficacy and safety of the pulsed radiofrequency (PRF) technique applied to the suprascapular nerve for the treatment of refractory shoulder pain. Methods: After obtaining Institutional Research Board approval and patients' written informed consent, patients with chronic shoulder pain resistant to medical treatment were included in prospective study and PRF technique was applied to the suprascapular nerve for 480 seconds. Verbal Numerical Rating Scale (VNRS) at 0, 3, and 6 months post procedure and Modified MacNab score before and 6 months after procedure are performed. Fifty percent or more decrease in VNRS and Modified MacNab score as Excellent and Good are accepted as a significant pain relief, 20 to 49% decrease is accepted as partial. Any complication related to procedure was also recorded. Results: Fifty-seven patients were included in the study. PRF treatment significantly relieved at the pain in 73.7% patients [42 patients out of 57]. Ten patients [17.5%] showed partial improvement and there were no changes at the pain scores in 5 patients [8.7%]. Forty-five patients [78.9%] showed improvement in VNRS scores as well as in Modified MacNab scores at 6 months after treatment. No side effects were reported. Pain scores were given as mean ± SD. Also, The Kaplan-Meier analysis was done for patients' shoulder pain after treatment with pulsed radiofrequency. Conclusion: Pulsed radiofrequency technique application to the suprascapular nerve for 480 seconds shows remarkable improvement at patients' chronic shoulder pain. © 2011 - IOS Press and the authors. All rights reserved.
Keywords: pulsed radiofrequency technique; Shoulder pain; treatment